2019
DOI: 10.1177/1012690219889621
|View full text |Cite
|
Sign up to set email alerts
|

Thinking beyond the binary: Barriers to trans* participation in university sport

Abstract: Sport is a significant part of university life in the UK, where students may try new sports for the first time. Research also demonstrates links between sport participation and mental health and employment prospects. Despite the positive aspects of university sports, by mimicking wider sport practices, they may also be environments that exclude non-normative bodies, including those who are trans*. The experiences of trans* people in sport is still a limited research area, with existing studies suggesting a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…This was explored by Treagus (2005), who analysed the history of netball as a 'suitable' sport for women which was codified to discourage roughness, over-competitiveness and 'too much' physical exertion, ensuring the game remained appropriately feminine. Therefore, sport has historically been a space grounded in dichotomous gender differences, with the socialisation of males and females into different sports still evident today, creating environments which are based upon stereotypical notions of gender (Phipps 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This was explored by Treagus (2005), who analysed the history of netball as a 'suitable' sport for women which was codified to discourage roughness, over-competitiveness and 'too much' physical exertion, ensuring the game remained appropriately feminine. Therefore, sport has historically been a space grounded in dichotomous gender differences, with the socialisation of males and females into different sports still evident today, creating environments which are based upon stereotypical notions of gender (Phipps 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As such, a small number of studies conducted in the UK and Finland question the safety of sport and physical education (PE) contexts for trans people (Berg & Kokkonen, 2021;Caudwell, 2007Caudwell, , 2014Hargie at al., 2017;Kokkonen, 2014;NUS, 2012a, b;Phipps, 2019Phipps, , 2020. Drawing on ethnographic and interview data gathered in the UK, Caudwell (2007Caudwell ( , 2014 found that significant barriers for trans participation emerge due to the general ignorance and prejudice surrounding transgender bodies and identities in sport.…”
Section: Transgender Inclusion In the Finnish And British Sport Contextmentioning
confidence: 99%
“…Despite calls for safe and inclusive environments in MACS, as well as in sport in general (Channon, 2014;Phipps, 2019Phipps, , 2020, we still lack knowledge on how transgender inclusion can actually be achieved. Indeed, there is a considerable lack of scholarly work focusing on transgender issues in MACS, with a few notable exceptions, such as the studies conducted by Fischer and McClearen (2020), Greey and Barker-Ruchti (2019), Love (2019), andMcClearen (2015).…”
mentioning
confidence: 99%
“…Recent studies (since 2015) demonstrate a number of items that cause exclusion of transgender participants from physical activity and sport. For example, changing/locker rooms, school sport, and public spaces (Hargie et al, 2017 ); how transgender people are imagined—by Spanish University sport science students—through tropes of abjection and alterity (Pérez-Samaniego et al, 2016 ); the binary arrangement of sport within UK University environment and policy (Phipps, 2019 ); both internal and external barriers and facilitators for young transgender adults (Jones et al, 2017b ); embodiment, fear, transitioning, social support, physical education, and how space is regulated (López-Cañada et al, 2019 ); the body, pre- and post-transition, stigma and pride (Elling-Machartzki, 2017 ); and identity, participation, competition, physical embodied change, and coming out (Klein et al, 2018 , 2019 ). Implicit to most existing studies is the element of safety and feeling safe.…”
Section: Inequality: Conceptual Framingmentioning
confidence: 99%